Garlic and ginger are not like apples and oranges: Effects of mass/count information on the production of noun phrases in English - Fieder, N.; Nickels, L.; Krajenbrink, T.; Biedermann, Britta (Routledge, 2018)
In this study a picture–word interference paradigm was used to investigate how grammatical mass/count information is processed during noun phrase production in English. Theories of lexical processing distinguish between two different types of lexical–syntactic information: variable extrinsic lexical–syntactic features, such as number (singular, plural), and fixed intrinsic lexical–syntactic properties, such as grammatical gender (e.g., masculine, feminine). Previous research using the picture–word interference paradigm has found effects of distractor lexical–syntactic congruency for grammatical gender but no congruency effects for number. We used this phenomenon to investigate whether mass/count information is processed similarly to grammatical gender. In two experiments, participants named pictures of mass or count objects using determiner noun phrases (e.g., Experiment 1 with mass and plural count nouns: “not muchmass ricemass”, “not manycount pegscount”; Experiment 2 with mass and singular count nouns: “some ricemass”, “a pegcount”), while ignoring distractors that were countability congruent or incongruent nouns. The results revealed a countability congruency effect for mass and plural count nouns in Experiment 1 and for singular count nouns, but not mass nouns in Experiment 2. This is similar to grammatical gender suggesting that countability processing is predominantly driven by a noun’s lexical–syntactic information. © 2017 The Experimental Psychology Society